2020
DOI: 10.21203/rs.3.rs-27351/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Affecting the Acceptance of Blended Learning in Medical Education: Application of UTAUT2 Model

Abstract: Background: Blended learning is a new approach toward improving the quality of medical education. Acceptance of blended learning plays an important role in its effective implementation. Therefore, the purpose of this study was to investigate and determine the factors that may influence the behavioral intention to use of blended learning in medical education.Methods: In this cross-sectional, correlational study, the sample consisted of 225 Iranian medical sciences students. The theoretical framework for designi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
4
19
0
Order By: Relevance
“…Instructor attitudes, such as being able to fully utilize the eLearning platform, keep answering questions, keep encouraging and motivating, were some key indicators that led to the utilization of the eLearning platform among medical students. These findings were also supported by Azizi [ 28 ], who also found that IC is a significant predictor of the intention to use the eLearning platform. Similarly, Roman and Plopeanu [ 33 ] also stressed the importance of the role of professors in the success of the learning process.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Instructor attitudes, such as being able to fully utilize the eLearning platform, keep answering questions, keep encouraging and motivating, were some key indicators that led to the utilization of the eLearning platform among medical students. These findings were also supported by Azizi [ 28 ], who also found that IC is a significant predictor of the intention to use the eLearning platform. Similarly, Roman and Plopeanu [ 33 ] also stressed the importance of the role of professors in the success of the learning process.…”
Section: Discussionsupporting
confidence: 76%
“…In SEM, statistical tests define the adequacy of model fit. We assessed how well the UTAUT2 theory fit the data gathered [ 26 , 28 ]. With prominent consideration of a theory, the most common change would be the deletion of a latent that does not meet the model fit or construct validity [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SGUS consisted of 30 items and four sub-scales of satisfaction, efficiency, helpfulness and learn ability. All items were rated on a 5-point Likert scale measure from strongly disagree [ 1 ] to strongly agree [ 5 ]. The overall range of scale scores was from 30 to 150.…”
Section: Methodsmentioning
confidence: 99%
“…E-learning is one of the most important phenomena in the digital age [ 1 , 2 ]. One of the emerging forms of information and communication technology (ICT) is virtual reality which has many applications in e-learning [ 3 ].…”
Section: Introductionmentioning
confidence: 99%